Psychosocial risk factors associated with lifetime Amphetamine-Type Stimulants (ATS) dependence in Drug Detention Centres: perspectives from the multiethnicity study. - Mamat, Ruzmayuddin; Abd. Rashid, Rusdi; Maw, Shin Sim; Ibrahim, Baharuddin; Wahab, Suzaily; Ahmad, Azmir (Taylor & Francis Online, 2023)
ATS dependence in Malaysia is growing tremendously across multiracial Malaysian groups, increasing concerns among public health experts and the community. This study highlighted the chronicity of ATS dependence and factors associated with ATS use. Interviewer-administered questionnaires were administered using ASSIST 3.0. A total of N = 327 multiracial people who use ATS were enrolled in this study. The study findings show that 190/327 (58.1%) respondents were ATS dependent. Malays reported the highest number of ATS-dependent (55.8%), followed by Bajau (21.6%) and Kadazan-Dusun (16.8%) ethnic. Across all races, three factors were significantly associated with the ATS dependence: respondents who had a lifetime history of needle sharing aOR = 0.023 (95% CI: 0.003, 0.183) and a lifetime history of heroin use aOR = 0.192 (95% CI: 0.093, 0.396) were at a reduced odd of ATS dependent. Meanwhile, being married reduced the likelihood of becoming dependent on ATS with aOR = 0.378 (95% CI: 0.206, 0.693) compared to being single or divorced. This study revealed that the use of ATS among multiracial Malaysians is alarmingly high, including those in detention centers. Comprehensive harm reduction strategies are urgently needed to prevent the spreading of infectious diseases and other negative health consequences associated with ATS use.